Callus induction and proliferation of Centella asiatica L. generated from leaves and petioles in the presence of Dicamba and BAP - Rahayu, Suci; Saptadi, Darmawan; Azmi, Chotimatul; Kusumanegara, Kusumawaty; Handayani, Tri; Roostika, Ika; Bermawie, Nurliani; Maulana, Haris (Universitas Padjadjaran, 2023)
Centella's need for industrial raw materials is high as a medicinal plant. These needs can be met through rapid multiplication using tissue culture techniques. In this study, induction and proliferation for a callus of centella cv. Castina 3 was conducted in the MS basal medium plus 4 mgL-1 Dicamba withand enriched with 7 concentrations of BAP (0, 0.1, 0.3, 0.5, 0.7, 0.9, and 1.1 mgL-1). Two kinds of explant were used, i.e., leaf and petiole. The results revealed that the addition of BAP in MS plus Dicamba medim stimulated better and produced a higher callus growth rate, both from leaf and petiole explants, than that media with Dicamba alone. Furthermore, 4 mgL-1 Dicamba + 1.1 mgL-1 BAP had a friable callus in the induction phase and a friable-compact callus in the proliferation phase. From this finding, it can be considered to use a combination of 4 mgL-1 Dicamba with 1.1 mgL-1 BAP in callus induction and proliferation for Centella rapid multiplication.